Relationship between tactical performance, somatic maturity and functional capabilities in young soccer players - Borges, P. H.; Cumming, S.; Ronque, E. R. V.; Cardoso, F.; Avelar, A.; Rechenchosky, L.; da Costa, I. T.; Rinaldi, W. (Journal of Human Kinetics, 2018)
The aim of the study was to investigate the relationship between tactical performance, somatic maturity, and functional capabilities in young soccer players. Study participants were 48 soccer players (14.80 ± 1.5 years) belonging to an extension project at the State University of Maringa - Brazil. Anthropometric measurements of body mass, body height, and sitting height were carried out. The number of years to peak height velocity (PHV) was used as an index of maturation. Evaluations of functional fitness included the following tests: sit-and-reach, Yo-Yo Intermittent Recovery Test Level 1, handgrip test, modified abdominal test, and vertical jumps (Counter Movement Jump and Jump Squat). Tactical performance was assessed through the System of Tactical Assessment in Soccer (FUT-SAT). Multiple Linear Regression models were used to estimate the relative contributions of functional and maturational capacities to tactical performance. The results indicated weak associations between the tactical performance indices and somatic maturity, functional capacity, and anthropometric attributes (r < 0.40). The Yo-Yo Test contributed to 36% of the defensive tactic performance variation in the under 13 category. These results suggest that the level of maturity, growth status, and functional fitness have limited impact on tactical performance of young soccer players.